2015
DOI: 10.1155/2015/810369
|View full text |Cite
|
Sign up to set email alerts
|

Hugan QingzhiExerts Anti-Inflammatory Effects in a Rat Model of Nonalcoholic Fatty Liver Disease

Abstract: Ethnopharmacological Relevance. The Hugan Qingzhi tablet (HQT) is a traditional Chinese medicine used for treating NAFLD (nonalcoholic fatty liver disease). The present study evaluated the anti-inflammatory effects of HQT in rats with NAFLD. Materials and Methods. HQT was administered daily to the NAFLD experimental groups. Biochemical markers, histopathological data, and oxidative stress/antioxidant biomarkers were determined. Proinflammatory cytokines interleukin-1β (IL-1β), tumor necrosis factor α (TNF-α), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Hugan Qingzhi (HQT) is a traditional Chinese medicine used for treatment of NAFLD. Its therapeutic effects on NAFLD have been confirmed in previous studies ( Yin et al, 2014 ; Tang et al, 2015 ). It consists mainly of five plant materials: including Rhizoma Alismatis, Fructus Crataegi, Pollen Typhae, Folium Nelumbinis, and Radix Notoginseng ( Yin et al, 2014 ).…”
Section: Introductionsupporting
confidence: 66%
“…Hugan Qingzhi (HQT) is a traditional Chinese medicine used for treatment of NAFLD. Its therapeutic effects on NAFLD have been confirmed in previous studies ( Yin et al, 2014 ; Tang et al, 2015 ). It consists mainly of five plant materials: including Rhizoma Alismatis, Fructus Crataegi, Pollen Typhae, Folium Nelumbinis, and Radix Notoginseng ( Yin et al, 2014 ).…”
Section: Introductionsupporting
confidence: 66%
“…The Hugan Qingzhi tablet (HQT) has a long history of use in alleviating NAFLD in clinical practice. In our previous in vitro and in vivo studies, it was confirmed that the HQT exerted lipid-lowering and anti-inflammatory effects on NAFLD [17, 18]. However, the relevant mechanism involved in its effect on ameliorating NAFLD requires further investigation.…”
Section: Introductionmentioning
confidence: 91%
“…It has been indicated that herbal medicine has exerted the protective effects against the progression from hepatic steatosis to steatohepatitis and the underlying mechanism have been proved to be involved in inhibiting the inflammatory signaling pathway as shown in Figure 2, thereby regulating dyslipidemia and improving liver function in NAFLD. Many herbal medicine (including herbal formula, crude extract and pure bioactive compound form medicinal plants) possessed antiinflammatory properties for slowing down the NAFLD progression, such as Sinai san dection (Zhang et al, 2005), Hugan Qingzhi tablet (Tang et al, 2015), betulinic acid (Kim et al, 2019b), Alisma orientalis , gastrodin (Ahmad et al, 2019), the peel extract of Citrus aurantium L. (Rutaceae) (Han et al, 2019) and swertiamarin (Yang Y. et al, FIGURE 1 | The lipid mechanistic insight into the anti-NAFLD effects of herbal medicine. NAFLD, Non-alcoholic fatty liver disease.…”
Section: Herbal Medicine Ameliorates the Hepatic Inflammationmentioning
confidence: 99%